Perovskite thin film, preparation method thereof, photoelectric device and preparation method thereof

By using inorganic metal cyanate as additives in perovskite solar cells, the problems of insufficient applicability and stability of perovskite components in the prior art have been solved, and the efficiency and stability of perovskite devices have been improved.

CN119136631APending Publication Date: 2024-12-13TRINA SOLAR CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411234927.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

During the preparation of perovskite solar cells, existing additives cannot be used for a wide range of perovskite components, resulting in difficult maintenance of device efficiency and stability. Long-chain ammonium salt additives can easily lead to the disappearance of 2D structure and the decrease of methylamino additive residues. stability.

Method used

Use inorganic metal cyanate as an additive to dopant into the perovskite crystal structure to reduce lattice defects and form a more stable crystal structure. It also forms a thin film by mixing inorganic metal cyanate with perovskite structural substances to form a thin film. Film-forming quality.

Benefits of technology

It significantly improves the efficiency and stability of perovskite devices, is suitable for different components and preparation processes, reduces lattice defects, and improves the film formation quality of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136631A_ABST
    Figure CN119136631A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite thin film, a preparation method thereof, a photoelectric device and a preparation method thereof, the perovskite thin film comprises a perovskite structure substance and inorganic metal cyanate, and metal in the inorganic metal cyanate is selected from one or more of alkali metal, alkaline earth metal, transition metal and rare earth metal. The perovskite thin film is high in film forming quality, and the photoelectric device comprising the perovskite thin film is high in efficiency and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of optoelectronics, and in particular relates to a perovskite film, a preparation method thereof, a photoelectric device and a preparation method thereof. Background Art

[0002] Organic-inorganic hybrid perovskite materials have the material advantages of high absorption coefficient, adjustable band gap, long carrier diffusion length, high defect tolerance, and industrial advantages of simple preparation process and low material and preparation costs. They are considered to be the new materials closest to commercialization in the photovoltaic market in recent years.

[0003] After only a dozen years of research, single-junction perovskite solar cells have achieved a high photoelectric conversion efficiency, surpassing the currently commercialized cadmium telluride and copper indium gallium selenide cells, and are very close to the mainstream crystalline silicon (26.7%) solar cells in the market. With its outstanding advantages such as high efficiency, low cost, and simple preparation process, stacked perovskite solar cells have gradually become a hot topic in the world's photovoltaic research field and are considered to be one of the technologies that are expected to achieve large-scale terrestrial photovoltaic applications.

[0004] In the preparation process of perovskite devices such as single-junction perovskite solar cells and stacked perovskite solar cells, how to prepare perovskite films with low defect state density is the key to achieving high-efficiency perovskite device preparation. However, the perovskite components are highly variable, and the additives for assisting film formation and crystallization are also different for perovskites of different components. The existing additives have different practicality for perovskites of different components and cannot be applied to a wide range of perovskite components. Long-chain ammonium salt additives can easily form 2D-structured perovskites in the bulk phase to improve device performance, but the two-dimensional perovskite diffuses into the bulk phase and disappears during photothermal aging, making it difficult to maintain the high efficiency of the device; additives containing methylamino (MA) will have a trace amount of residue during the annealing process, and the residual MA will significantly reduce the stability of the device, affecting the practicality of the final product.

[0005] Therefore, there is an urgent need to develop a perovskite film with new additives to improve the efficiency and stability of perovskite devices with different components or different preparation processes. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a perovskite film, which comprises a perovskite structure material and an inorganic metal cyanate. By adding an inorganic metal cyanate additive to a solution containing a perovskite structure material, the film-forming quality of the perovskite thin film can be significantly improved, thereby improving the efficiency of the device; and specific inorganic metal ions can be doped into the perovskite crystal structure to reduce lattice defects and form a more stable crystal structure, thereby improving the stability of the device. In summary, the perovskite film of the present invention can effectively improve the efficiency and stability of perovskite devices with different components or different preparation processes.

[0007] Specifically, the present invention provides a perovskite film, which comprises a perovskite structure material and an inorganic metal cyanate, wherein the metal in the inorganic metal cyanate is selected from one or more of an alkali metal, an alkaline earth metal, a transition metal and a rare earth metal.

[0008] In one or more embodiments, the inorganic metal cyanate is selected from one or more of lithium cyanate, sodium cyanate, potassium cyanate, rubidium cyanate, cesium cyanate, magnesium cyanate, calcium cyanate, barium cyanate, zinc cyanate, cobalt cyanate, copper cyanate, europium cyanate, cerium cyanate and lanthanum cyanate.

[0009] In one or more embodiments, the chemical formula of the perovskite structured material is ABX3, wherein A is a monovalent cation including one or more of cesium, rubidium, methylamine and methylamidine, B is a divalent cation including one or more of lead, copper, zinc, gallium, tin and calcium, and X is a monovalent anion including one or more of iodine, bromine, chlorine, fluorine, thiocyanate, tetrafluoroborate, hexafluorophosphate, formate and acetate.

[0010] In one or more embodiments, the mass ratio of the inorganic metal cyanate to the perovskite structured material is ≤5.5%, preferably 1:(50-10000000).

[0011] In one or more embodiments, the thickness of the perovskite film is 200 to 10000 nm.

[0012] The present invention provides a method for preparing the perovskite film of the present invention, the method comprising the following steps: mixing raw materials of a perovskite structural material and an inorganic metal cyanate in a solvent to prepare a perovskite precursor solution, and depositing the perovskite precursor solution to obtain a perovskite film.

[0013] In one or more embodiments, in the perovskite precursor solution, the solvent is selected from N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, 2-methoxyethanol, ethanol

[0014] and isopropyl alcohol.

[0015] In one or more embodiments, in the perovskite precursor solution, the method of depositing the perovskite precursor solution is spin coating, blade coating, electron beam evaporation, thermal evaporation, printing, spraying, spray pyrolysis or slot coating.

[0016] In one or more embodiments, in the perovskite precursor solution, the concentration of the inorganic metal cyanate in the perovskite precursor solution is 0.002-20 mg / mL.

[0017] The present invention provides a photoelectric device, which comprises a perovskite film, wherein the perovskite film comprises a perovskite structural material and an inorganic metal cyanate; preferably, the photoelectric device is a perovskite solar cell device, an LED device or a detector device.

[0018] In one or more embodiments, the perovskite solar cell device includes a single-junction perovskite solar cell and / or a stacked perovskite solar cell. In one or more embodiments, the single-junction perovskite solar cell is a formal single-junction perovskite solar cell or an inverted single-junction perovskite solar cell, and the formal single-junction perovskite solar cell includes transparent conductive glass, an electron transport layer, a perovskite thin film layer, a hole transport layer and a back electrode from the light-receiving front to the light-receiving back; the inverted single-junction perovskite solar cell includes transparent conductive glass, a hole transport layer, a perovskite thin film layer, an electron transport layer and a back electrode from the light-receiving front to the light-receiving back.

[0019] In one or more embodiments, the tandem perovskite solar cell is a formal tandem perovskite solar cell or an inverted tandem perovskite solar cell, wherein the inverted tandem perovskite solar cell includes, from the light-receiving front side to the light-receiving back side, a top electrode, an inverted perovskite top cell, a tunneling layer, a bottom cell and a back electrode in sequence, and the inverted perovskite top cell includes, from the light-receiving front side to the light-receiving back side, an electron transport layer, a perovskite thin film layer and a hole transport layer in sequence; the formal tandem perovskite solar cell includes, from the light-receiving front side to the light-receiving back side, a top electrode, a formal perovskite top cell, a tunneling layer, a bottom cell and a back electrode in sequence; the inverted perovskite top cell includes, from the light-receiving front side to the light-receiving back side, a hole transport layer, a perovskite thin film layer and an electron transport layer in sequence.

[0020] In one or more embodiments, the top electrode includes a transparent electrode layer; preferably, the top electrode includes a gate electrode and a transparent electrode layer in sequence from the light-receiving front side to the light-receiving back side; more preferably, the top electrode includes a gate electrode, an anti-reflection layer and a transparent electrode layer in sequence from the light-receiving front side to the light-receiving back side; wherein the material of the transparent electrode layer is preferably selected from one or more of indium tin oxide, indium zinc oxide, cerium-doped indium oxide, tungsten-doped indium oxide, aluminum-doped zinc oxide, antimony-doped tin oxide, zirconium-doped indium oxide and gallium zinc-doped indium oxide; the material of the gate electrode is preferably silver and / or copper; the material of the anti-reflection layer is preferably selected from one or more of silicon oxide, aluminum oxide, silicon nitride, magnesium fluoride, lithium fluoride, polydimethylsiloxane and ethylene-vinyl acetate copolymer; the thickness of the top electrode is preferably 0.005-201 μm; the thickness of the transparent electrode layer is 5-300 nm; the thickness of the gate electrode is preferably 0-200 μm; the thickness of the anti-reflection layer is preferably 0-400 nm.

[0021] In one or more embodiments, the transparent conductive glass is indium tin oxide glass, indium zinc oxide glass, cerium-doped indium oxide glass, tungsten-doped indium oxide glass, aluminum-doped zinc oxide glass, antimony-doped tin oxide glass, zirconium-doped indium oxide glass, or gallium zinc-doped indium oxide glass.

[0022] In one or more embodiments, the hole transport layer is made of an inorganic transport material and / or a p-type semiconductor material; preferably, the inorganic transport material is selected from one or more of nickel oxide, cuprous oxide, molybdenum oxide and copper iodide; the p-type semiconductor material is selected from one or more of redox graphene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, poly-3,4-ethylenedioxythiophene, polystyrene sulfonate, poly[bis(4-phenyl)(4-butylphenyl)amine], [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid.

[0023] In one or more embodiments, the electron transport layer is made of an n-type semiconductor material; preferably, the n-type semiconductor material is selected from one or more of titanium oxide, tin oxide, zinc oxide, fullerene, graphene and fullerene derivatives.

[0024] In one or more embodiments, the tunneling layer material is indium tin oxide, indium zinc oxide, cerium-doped indium oxide, tungsten-doped indium oxide, aluminum-doped zinc oxide, antimony-doped tin oxide, zirconium-doped indium oxide, gallium-zinc-doped indium oxide, a combination of heavily doped n-silicon and p-silicon, or a combination of n-silicon and other p-type materials; preferably, other p-type materials are MoO3 and / or NiOx.

[0025] In one or more embodiments, the bottom cell is a perovskite bottom cell, a crystalline silicon bottom cell, a copper indium gallium selenide bottom cell, a gallium arsenide bottom cell, a cadmium telluride bottom cell, an organic bottom cell or a quantum dot bottom cell.

[0026] In one or more embodiments, the back electrode material is selected from one or more of gold, palladium, silver, titanium, chromium, nickel, aluminum, copper, indium tin oxide and indium zinc oxide.

[0027] In one or more embodiments, in the single-junction perovskite solar cell, the thickness of the hole transport layer is 0.2-100 nm.

[0028] In one or more embodiments, in the single-junction perovskite solar cell, the thickness of the perovskite thin film layer is 200-3000 nm.

[0029] In one or more embodiments, in the single-junction perovskite solar cell, the thickness of the electron transport layer is 1-90 nm.

[0030] In one or more embodiments, in the single-junction perovskite solar cell, the thickness of the back electrode is 0.04-200 μm.

[0031] In one or more embodiments, in the tandem perovskite solar cell, the thickness of the hole transport layer is 0.2-100 nm.

[0032] In one or more embodiments, in the tandem perovskite solar cell, the thickness of the perovskite thin film layer is 200-3000 nm.

[0033] In one or more embodiments, in the tandem perovskite solar cell, the thickness of the electron transport layer is 0.5-90 nm.

[0034] In one or more embodiments, in the tandem perovskite solar cell, the thickness of the bottom cell is 10-600 μm.

[0035] In one or more embodiments, in the tandem perovskite solar cell, the thickness of the back electrode is 0.04-100 μm.

[0036] The present invention provides a method for preparing the optoelectronic device of the present invention, the method comprising the following steps:

[0037] (1) depositing a hole transport layer or an electron transport layer on the surface of the transparent conductive glass;

[0038] (2) depositing a perovskite thin film layer on the surface of the hole transport layer or the electron transport layer;

[0039] (3) depositing an electron transport layer or a hole transport layer on the surface of the perovskite thin film layer;

[0040] (4) depositing a back electrode on the surface of the electron transport layer or the hole transport layer to obtain a single-junction perovskite solar cell; or

[0041] (1') depositing a back electrode material and a tunneling layer on two surfaces of the bottom cell respectively;

[0042] (2') Depositing a hole transport layer or an electron transport layer on the surface of the tunnel layer

[0043] (3') depositing a perovskite thin film layer on the surface of the hole transport layer or the electron transport layer;

[0044] (4') depositing an electron transport layer or a hole transport layer on the surface of the perovskite thin film layer;

[0045] (5') depositing a top electrode on the surface of the electron transport layer or the hole transport layer to obtain a stacked perovskite solar cell.

[0046] In one or more embodiments, in step (2) or step (3') of preparing a photoelectric device, a perovskite precursor solution is deposited on the surface of a hole transport layer or an electron transport layer to obtain a perovskite thin film layer, wherein the perovskite precursor solution includes a raw material of a perovskite structure material, an inorganic metal cyanate and a solvent.

[0047] In one or more embodiments, in the method for preparing a photoelectric device, the method for preparing the perovskite precursor solution is: mixing the raw materials of the perovskite structure material and the inorganic metal cyanate in a solvent to prepare the perovskite precursor solution.

[0048] In one or more embodiments, in the method for preparing an optoelectronic device, the solvent in the perovskite precursor solution is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide N-methylpyrrolidone, acetonitrile, 2-methoxyethanol, ethanol and isopropanol.

[0049] In one or more embodiments, in the method for preparing an optoelectronic device, the concentration of the inorganic metal cyanate in the perovskite precursor solution is 0.002-20 mg / mL.

[0050] The present invention provides a method for preparing the single-junction perovskite solar cell of the present invention, the method comprising the following steps:

[0051] (1) depositing a hole transport layer material on the surface of the transparent conductive glass to obtain a hole transport layer;

[0052] (2) depositing a perovskite precursor solution on the surface of the hole transport layer to obtain a perovskite thin film layer;

[0053] (3) depositing an electron transport layer material on the surface of the perovskite thin film layer to obtain an electron transport layer;

[0054] (4) depositing a back electrode material on the surface of the electron transport layer to obtain a back electrode and an inverted single-junction perovskite solar cell; or

[0055] (1') depositing an electron transport layer material on the surface of the transparent conductive glass to obtain an electron transport layer;

[0056] (2') depositing a perovskite precursor solution on the surface of the electron transport layer to obtain a perovskite thin film layer;

[0057] (3') depositing a hole transport layer material on the surface of the perovskite film layer to obtain a hole transport layer;

[0058] (4') Depositing a back electrode material on the surface of the hole transport layer to obtain a back electrode and a formal single-junction perovskite solar cell.

[0059] In one or more embodiments, in the method for preparing a single-junction perovskite solar cell, the hole transport layer is deposited by spin coating, scraping, physical vapor deposition, atomic layer deposition, slit coating or immersion; preferably, the physical vapor deposition is magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0060] In one or more embodiments, in the method for preparing a single-junction perovskite solar cell, the method for preparing the perovskite precursor solution is: mixing the raw materials of the perovskite structure material and the inorganic metal cyanate in a solvent to prepare the perovskite precursor solution.

[0061] In one or more embodiments, in the method for preparing a single-junction perovskite solar cell, the solvent in the perovskite precursor solution is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide N-methylpyrrolidone, acetonitrile, 2-methoxyethanol, ethanol and isopropanol.

[0062] In one or more embodiments, in the method for preparing a single-junction perovskite solar cell, the concentration of the inorganic metal cyanate in the perovskite precursor solution is 0.002-20 mg / mL.

[0063] In one or more embodiments, in the method for preparing a single-junction perovskite solar cell, the deposition method of the perovskite thin film layer is spin coating, blade coating, electron beam evaporation, thermal evaporation, printing, spraying, spray pyrolysis or slot coating.

[0064] In one or more embodiments, in the method for preparing a single-junction perovskite solar cell, the electron transport layer is deposited by spin coating, scraping, physical vapor deposition, atomic layer deposition, slit coating or immersion; preferably, the physical vapor deposition is magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0065] In one or more embodiments, in the method for preparing a single-junction perovskite solar cell, the back electrode is deposited by physical vapor deposition, printing, spraying or electroplating; preferably, the physical vapor deposition is magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0066] The present invention provides a method for preparing the tandem perovskite solar cell of the present invention, the method comprising the following steps:

[0067] (1) depositing a back electrode material and a tunneling layer material on two surfaces of the bottom battery respectively to obtain a back electrode and a tunneling layer;

[0068] (2) depositing a hole transport layer material on the surface of the tunnel layer to obtain a hole transport layer;

[0069] (3) depositing a perovskite precursor solution on the surface of the hole transport layer to obtain a perovskite thin film layer;

[0070] (4) depositing an electron transport layer material on the surface of the perovskite thin film layer to obtain an electron transport layer;

[0071] (5) depositing a top electrode material on the surface of the electron transport layer to obtain an inverted stacked perovskite solar cell while obtaining the top electrode; or

[0072] (1') depositing a back electrode material and a tunneling layer material on two surfaces of the bottom battery respectively to obtain a back electrode and a tunneling layer;

[0073] (2') depositing an electron transport layer material on the surface of the tunneling layer to obtain an electron transport layer;

[0074] (3') depositing a perovskite precursor solution on the surface of the electron transport layer to obtain a perovskite thin film layer;

[0075] (4′) depositing a hole transport layer material on the surface of the perovskite thin film layer to obtain a hole transport layer;

[0076] (5') depositing a top electrode material on the surface of the hole transport layer to obtain a top electrode and a formal laminated perovskite solar cell;

[0077] The top electrode includes a transparent electrode layer; preferably, the top electrode includes a gate electrode and a transparent electrode layer in sequence from the light-receiving front side to the light-receiving back side, and more preferably, the top electrode includes a gate electrode, an anti-reflection layer and a transparent electrode layer in sequence from the light-receiving front side to the light-receiving back side.

[0078] In one or more embodiments, in the method for preparing a stacked perovskite solar cell, the back electrode is deposited by physical vapor deposition, printing, spraying or electroplating; preferably, the physical vapor deposition is magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0079] In one or more embodiments, in the method for preparing a stacked perovskite solar cell, the tunneling layer is deposited by physical vapor deposition, single atomic layer deposition, chemical vapor deposition or plasma enhanced chemical vapor deposition; preferably, the physical vapor deposition is magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0080] In one or more embodiments, in the method for preparing a stacked perovskite solar cell, the hole transport layer is deposited by spin coating, scraping, physical vapor deposition, atomic layer deposition, slit coating or immersion; preferably, the physical vapor deposition is magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0081] In one or more embodiments, in the method for preparing a stacked perovskite solar cell, the method for preparing the perovskite precursor solution is: mixing the raw materials of the perovskite structure material and the inorganic metal cyanate in a solvent to prepare the perovskite precursor solution.

[0082] In one or more embodiments, in the method for preparing a tandem perovskite solar cell, the solvent in the perovskite precursor solution is selected from N,N-dimethylformamide, dimethyl sulfoxide, N-methyl

[0083] One or more of 1,2-dimethylpyrrolidone, acetonitrile, 2-methoxyethanol, ethanol and isopropanol.

[0084] In one or more embodiments, in the method for preparing a tandem perovskite solar cell, the concentration of the inorganic metal cyanate in the perovskite precursor solution is 0.002-20 mg / mL.

[0085] In one or more embodiments, in the method for preparing a tandem perovskite solar cell, the deposition method of the perovskite thin film layer is spin coating, blade coating, electron beam evaporation, thermal evaporation, printing, spraying, spray pyrolysis or slit coating.

[0086] In one or more embodiments, in the method for preparing a stacked perovskite solar cell, the electron transport layer is deposited by spin coating, scraping, physical vapor deposition, atomic layer deposition, slit coating or immersion; preferably, the physical vapor deposition is magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0087] In one or more embodiments, in the method for preparing a stacked perovskite solar cell, the transparent electrode layer is deposited by physical vapor deposition; preferably, the physical vapor deposition is magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0088] In one or more embodiments, in the method for preparing a stacked perovskite solar cell, the anti-reflection layer is deposited by physical vapor deposition; preferably, the physical vapor deposition is magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0089] In one or more embodiments, in the method for preparing a tandem perovskite solar cell, the grid line electrode is deposited by thermal evaporation, printing or electroplating. BRIEF DESCRIPTION OF THE DRAWINGS

[0090] Figure 1 (a) is a schematic diagram of the structure of a single-junction perovskite solar cell according to some embodiments of the present invention.

[0091] Figure 1 (b) is a schematic diagram of the structure of a tandem perovskite solar cell according to some embodiments of the present invention.

[0092] Figure 1 (c) is a schematic diagram of the detailed structure of a tandem perovskite solar cell according to some embodiments of the present invention.

[0093] Figure 2 Schematic diagram of the structure of inorganic metal cyanate in some embodiments of the present invention; Figure 2 Among them, (a) lithium cyanate, (b) sodium cyanate, (c) potassium cyanate, (d) rubidium cyanate, (e) cesium cyanate,

[0094] (f) magnesium cyanate, (g) calcium cyanate, (h) barium cyanate, (i) zinc cyanate, (j) copper cyanate, (k) cobalt cyanate, (l) europium cyanate, (m) cerium cyanate, (n) lanthanum cyanate.

[0095] Figure 3 Schematic diagram of crystalline silicon / perovskite tandem solar cells according to some embodiments of the present invention.

[0096] Figure 4 The X-ray diffraction patterns (XRD) of the perovskite films prepared in Examples 1-3, Example 6, Examples 8-9 and Comparative Example 1 of the present invention are shown.

[0097] Figure 5 The fluorescence images of the perovskite films prepared in Examples 1-9 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0098] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0099] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0100] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0101] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0102] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0103] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0104] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0105] The present invention provides a perovskite film, which comprises a perovskite structure material and an inorganic metal cyanate, wherein the metal in the inorganic metal cyanate may be one or more selected from alkali metals, alkaline earth metals, transition metals and rare earth metals. In the present invention, by adding an inorganic metal cyanate additive to a solution containing a perovskite structure material, the film-forming quality of the perovskite thin film can be significantly improved, thereby improving the efficiency of the device; and specific inorganic metal ions can be doped into the perovskite crystal structure to reduce lattice defects and form a more stable crystal structure, thereby improving the stability of the perovskite device. In summary, the perovskite film of the present invention can effectively improve the efficiency and stability of perovskite devices with different components or different preparation processes.

[0106] In the present invention, the inorganic metal cyanate may be one or more selected from lithium cyanate, sodium cyanate, potassium cyanate, rubidium cyanate, cesium cyanate, magnesium cyanate, calcium cyanate, barium cyanate, zinc cyanate, cobalt cyanate, copper cyanate, europium cyanate, cerium cyanate and lanthanum cyanate, and its structure is as follows: Figure 2 In the present invention, the inorganic metal cyanate additive improves the quality of perovskite film crystallization of different components and the quality of perovskite film crystallization of different process methods.

[0107] In the present invention, the chemical formula of the perovskite structure material can be ABX3, wherein A can be a monovalent cation, including cesium (Cs + ), rubidium (Rb + ), methylamino (CH3NH3 + , MA) and carbamimidyl (CH(NH)NH2 + , FA), B can be a divalent cation, including lead (Pb 2+ ), copper (Cu 2+ )、Zn 2+ ), gallium (Ga 2+ ), tin (Sn 2+ ) and calcium (Ca 2+ ), X can be a monovalent anion, including iodine (I - ), bromine (Br - ), chlorine (Cl - ), fluorine (F - ), thiocyanate (SCN - ), tetrafluoroborate (BF4 - ), hexafluorophosphate (PF6 - ), formate (COO - ) and acetate (CH3COO - The inorganic metal cyanate of the present invention improves the quality of film crystallization of thin films formed by perovskite structure materials of different components, and further, significantly improves the efficiency and stability of devices composed of thin films of different perovskite structure materials.

[0108] In the present invention, the mass ratio of the inorganic metal cyanate to the perovskite structure material can be ≤5.5%, preferably

[0109] The mass ratio of inorganic metal cyanate to perovskite structure material is controlled within the above preferred range, which is beneficial to the film-forming crystal quality of the perovskite film, and further beneficial to improving the efficiency and stability of the optoelectronic device containing the perovskite film.

[0110] In the present invention, the thickness of the perovskite film can be 200 to 10000 nm, for example, 200 nm, 500 nm, 1000 nm, 2000 nm, 3000 nm, 4000 nm, 5000 nm, 6000 nm, 7000 nm, 8000 nm, 9000 nm, and 10000 nm.

[0111] The invention provides a method for preparing the perovskite film of the invention, the method comprising the following steps: mixing raw materials of a perovskite structural material and an inorganic metal cyanate in a solvent to prepare a perovskite precursor solution, and depositing the perovskite precursor solution to obtain a perovskite film.

[0112] In the method for preparing the perovskite film of the present invention, the solvent can be one or more selected from N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone, acetonitrile, 2-methoxyethanol, ethanol and isopropanol.

[0113] In the method for preparing the perovskite film of the present invention, the method for depositing the perovskite precursor solution can be spin coating, blade coating, electron beam evaporation, thermal evaporation, printing, spraying, spray pyrolysis or slit coating. The inorganic metal cyanate of the present invention improves the quality of film crystallization of perovskite films prepared by different processes, and further, significantly improves the efficiency and stability of devices composed of perovskite films prepared by different processes.

[0114] In the present invention, the concentration of the inorganic metal cyanate in the perovskite precursor solution is 0.002-20 mg / mL, such as 0.005 mg / mL, 0.01 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 5 mg / mL, 10 mg / mL, 15 mg / mL, 20 mg / mL. The present invention controls the concentration of the inorganic metal cyanate in the perovskite precursor solution within the above range, which is beneficial to the film-forming crystal quality of the perovskite film, and further helps to improve the efficiency and stability of the optoelectronic device containing the perovskite film.

[0115] The present invention provides a photoelectric device comprising the perovskite film of the present invention; preferably, the photoelectric device is a perovskite solar cell device, an LED device or a detector device; more preferably, the perovskite

[0116] The solar cell device is a single-junction perovskite solar cell or a tandem perovskite solar cell. In some embodiments, the tandem perovskite solar cell is a perovskite / perovskite tandem cell, a perovskite / crystalline silicon tandem cell, a perovskite / copper indium gallium selenide tandem cell, a perovskite / gallium arsenide tandem cell, a perovskite / cadmium telluride tandem cell, a perovskite / organic tandem cell, or a perovskite / quantum dot tandem cell. In the present invention, the single-junction perovskite solar cell is a formal single-junction perovskite solar cell or an inverted single-junction perovskite solar cell, and the formal single-junction perovskite solar cell includes a transparent conductive glass, an electron transport layer, a perovskite thin film layer, a hole transport layer, and a back electrode (such as Figure 1 (a)); the inverted single-junction perovskite solar cell includes a transparent conductive glass, a hole transport layer, a perovskite film layer, an electron transport layer and a back electrode (as shown in FIG. Figure 1 (a)). The single-junction perovskite solar cell of the present invention has a perovskite thin film layer containing an inorganic metal cyanate, which is beneficial to improving the efficiency and stability of the single-junction perovskite solar cell.

[0117] In the present invention, the tandem perovskite solar cell is a formal tandem perovskite solar cell or an inverted tandem perovskite solar cell. The inverted tandem perovskite solar cell comprises a top electrode, an inverted perovskite top cell, a tunneling layer, a bottom cell and a back electrode (such as Figure 1 (b) shows), the inverse perovskite top cell includes an electron transport layer, a perovskite film layer, a hole transport layer (as shown in FIG. Figure 1 (c)); the formal stacked perovskite solar cell includes a top electrode, a formal perovskite top cell, a tunneling layer, a bottom cell and a back electrode from the light-receiving front side to the light-receiving back side (as shown in FIG. Figure 1 (b)); the inverse perovskite top cell includes a hole transport layer, a perovskite thin film layer, an electron transport layer (as shown in FIG. Figure 1 (c)). The tandem perovskite solar cell of the present invention has a perovskite film layer containing an inorganic metal cyanate, which is beneficial to improving the efficiency and stability of the tandem perovskite solar cell.

[0118] In the present invention, the top electrode may include a transparent electrode layer; preferably, the top electrode includes a gate electrode and a transparent electrode layer in sequence from the light-receiving front side to the light-receiving back side; more preferably, the top electrode includes a gate electrode, an anti-reflection layer and a transparent electrode layer in sequence from the light-receiving front side to the light-receiving back side.

[0119] In the top electrode of the present invention, the material of the transparent electrode layer can be one or more selected from indium tin oxide (ITO), indium zinc oxide (IZO), cerium-doped indium oxide (ICO), tungsten-doped indium oxide (IWO), aluminum-doped zinc oxide (AZO), antimony-doped tin oxide (ATO), zirconium-doped indium oxide (IZrO) and gallium-zinc-doped indium oxide (IGZO).

[0120] In the top electrode of the present invention, the gate line electrode may be silver and / or copper.

[0121] In the top electrode of the present invention, the antireflection layer can be one or more selected from silicon oxide, aluminum oxide, silicon nitride, magnesium fluoride, lithium fluoride, polydimethylsiloxane (PDMS) or ethylene-vinyl acetate copolymer (EVA).

[0122] In the top electrode of the present invention, the thickness of the transparent electrode layer can be 5-300nm, for example, 5nm, 10nm, 30nm, 60nm, 90nm, 120nm, 150nm, 180nm, 210nm, 240nm, 270nm, 300nm.

[0123] In the top electrode of the present invention, the thickness of the gate line electrode may be 0-200 μm, for example, 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, or 200 μm.

[0124] In the top electrode of the present invention, the thickness of the antireflection layer can be 0-400nm, for example, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 150nm, 180nm, 210nm, 240nm, 270nm, 300nm.

[0125] In the top electrode of the present invention, the thickness of the top electrode can be 0.005-201 μm. In some embodiments, the top electrode is composed of a transparent electrode layer, and the thickness of the top electrode is the thickness of the transparent electrode layer, and the thickness range is 5-300 nm. In some embodiments, the top electrode is composed of a gate electrode and a transparent electrode layer, and the thickness of the top electrode is the sum of the thickness of the gate electrode and the transparent electrode layer, and the thickness range is 0.005-200.3 μm. In some embodiments, it is composed of a gate electrode, an anti-reflection layer and a transparent electrode layer, and the thickness of the top electrode is the sum of the thickness of the gate electrode, the anti-reflection layer and the transparent electrode layer, and the thickness range is 0.005-200.7 μm.

[0126] In the present invention, the transparent conductive glass can be indium tin oxide glass, indium zinc oxide glass, cerium-doped indium oxide glass, tungsten-doped indium oxide glass, aluminum-doped zinc oxide glass, antimony-doped tin oxide glass, zirconium-doped indium oxide glass or gallium zinc-doped indium oxide glass.

[0127] In the present invention, the hole transport layer material can be an inorganic transport material and / or a p-type semiconductor material; preferably, the inorganic transport material can be one or more selected from nickel oxide (NiO), cuprous oxide (Cu2O), molybdenum oxide (MoO3) and copper iodide (CuI); the p-type semiconductor material can be selected from redox graphene, poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA), 2,2',7,7'-tetrakis [N,N-di (4-methoxyphenyl) amino] -9,9'-spirobifluorene (Spiro-OMeTAD), poly 3,4-ethylenedioxythiophene (PEDOT), polystyrene sulfonate (PSS), poly [bis (4-phenyl) (4-butylphenyl)

[0128] amine] (Ploy-TPD), [2-(9H-carbazol-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid (MeO-2PACZ) One or more.

[0129] In the present invention, the material of the electron transport layer can be an n-type semiconductor material; preferably, the n-type semiconductor material can be one or more selected from titanium oxide (TiO2), tin oxide (SnO2), zinc oxide (ZnO), fullerene (C60), graphene and fullerene derivatives (PCBM). In some embodiments, the fullerene derivative is [6,6]-phenyl-C61-butyric acid isomethyl ester (

[60] PCBM); in some embodiments, the fullerene derivative is [6,6]-phenyl-C71-butyric acid isomethyl ester (

[70] PCBM).

[0130] In the present invention, the tunneling layer material can be indium tin oxide, indium zinc oxide, cerium-doped indium oxide, tungsten-doped indium oxide, aluminum-doped zinc oxide, antimony-doped tin oxide, zirconium-doped indium oxide, gallium zinc-doped indium oxide, a combination of heavily doped n-silicon and p-silicon, or a combination of n-silicon and other p-type materials; preferably, other p-type materials are MoO3 and / or NiOx.

[0131] In the present invention, the bottom cell may be a perovskite bottom cell, a crystalline silicon bottom cell, a copper indium gallium selenide bottom cell, a gallium arsenide bottom cell, a cadmium telluride bottom cell, an organic bottom cell or a quantum dot bottom cell.

[0132] In the present invention, the material of the back electrode may be one or more selected from the group consisting of gold, palladium, silver, titanium, chromium, nickel, aluminum, copper, indium tin oxide (ITO) and indium zinc oxide (IZO).

[0133] In the single-junction perovskite solar cell of the present invention, the thickness of the hole transport layer can be 0.2-100 nm, for example, 0.5 nm, 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm.

[0134] In the single-junction perovskite solar cell of the present invention, the thickness of the perovskite thin film layer can be 200-3000nm, for example, 200nm, 400nm, 600nm, 800nm, 1000nm, 1200nm, 1400nm, 1600nm, 1800nm, 2000nm, 2200nm, 2400nm, 2600nm, 2800nm, and 3000nm.

[0135] In the single-junction perovskite solar cell of the present invention, the thickness of the electron transport layer can be 1-90 nm, for example, 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm.

[0136] In the single-junction perovskite solar cell of the present invention, the thickness of the back electrode can be 0.04-200 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 50 μm, 100 μm, 150 μm, or 200 μm.

[0137] In the stacked perovskite solar cell of the present invention, the thickness of the hole transport layer can be 0.2-100 nm, for example, 0.5 nm, 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm.

[0138] In the stacked perovskite solar cell of the present invention, the thickness of the perovskite thin film layer can be 200-3000nm, for example, 200nm, 400nm, 600nm, 800nm, 1000nm, 1200nm, 1400nm, 1600nm, 1800nm, 2000nm.

[0139] In the stacked perovskite solar cell of the present invention, the thickness of the electron transport layer can be 0.5-90nm, for example, 1nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm.

[0140] In the stacked perovskite solar cell of the present invention, the thickness of the bottom cell can be 10-600μm, for example, 20μm, 50μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm, 450μm, 500μm, 550μm, 600μm.

[0141] In the stacked perovskite solar cell of the present invention, the thickness of the back electrode can be 0.04-100 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 50 μm, 100 μm, 150 μm, and 200 μm.

[0142] The present invention provides a method for preparing a photoelectric device, the method comprising the following steps:

[0143] (1) depositing a hole transport layer or an electron transport layer on the surface of the transparent conductive glass;

[0144] (2) depositing a perovskite thin film layer on the surface of the hole transport layer or the electron transport layer;

[0145] (3) depositing an electron transport layer or a hole transport layer on the surface of the perovskite thin film layer;

[0146] (4) depositing a back electrode on the surface of the electron transport layer or the hole transport layer to obtain a single-junction perovskite solar cell; or

[0147] (1') depositing a back electrode material and a tunneling layer on two surfaces of the bottom cell respectively;

[0148] (2') Depositing a hole transport layer or an electron transport layer on the surface of the tunnel layer

[0149] (3') depositing a perovskite thin film layer on the surface of the hole transport layer or the electron transport layer;

[0150] (4') depositing an electron transport layer or a hole transport layer on the surface of the perovskite thin film layer;

[0151] (5') depositing a top electrode on the surface of the electron transport layer or the hole transport layer to obtain a stacked perovskite solar cell.

[0152] In the step (2) or step (3') of preparing the optoelectronic device of the present invention, a perovskite precursor solution is deposited on the surface of the hole transport layer or the electron transport layer to obtain a perovskite film layer. The perovskite precursor solution includes a raw material of a perovskite structure material, an inorganic metal cyanate and a solvent.

[0153] In the method for preparing a photoelectric device of the present invention, the preparation method of the perovskite precursor solution can be: mixing the raw materials of the perovskite structure material and the inorganic metal cyanate in a solvent to prepare the perovskite precursor solution.

[0154] In the method for preparing a photoelectric device of the present invention, the solvent in the perovskite precursor solution can be one or more selected from N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, 2-methoxyethanol, ethanol and isopropanol.

[0155] In the method for preparing a photoelectric device of the present invention, the concentration of the inorganic metal cyanate in the perovskite precursor solution can be 0.002-20 mg / mL, such as 0.005 mg / mL, 0.01 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 5 mg / mL, 10 mg / mL, 15 mg / mL, 20 mg / mL. The present invention controls the concentration of the inorganic metal cyanate in the perovskite precursor solution within the above range, which is beneficial to the film-forming crystal quality of the perovskite film, and further helps to improve the efficiency and stability of the photoelectric device comprising the perovskite film.

[0156] The present invention provides a method for preparing a single-junction perovskite solar cell of the present invention, the method comprising the following steps:

[0157] (1) depositing a hole transport layer material on the surface of the transparent conductive glass to obtain a hole transport layer;

[0158] (2) depositing a perovskite precursor solution on the surface of the hole transport layer to obtain a perovskite thin film layer;

[0159] (3) depositing an electron transport layer material on the surface of the perovskite thin film layer to obtain an electron transport layer;

[0160] (4) depositing a back electrode material on the surface of the electron transport layer to obtain a back electrode and an inverted single-junction perovskite solar cell; or

[0161] (1') depositing an electron transport layer material on the surface of the transparent conductive glass to obtain an electron transport layer;

[0162] (2') depositing a perovskite precursor solution on the surface of the electron transport layer to obtain a perovskite thin film layer;

[0163] (3') depositing a hole transport layer material on the surface of the perovskite film layer to obtain a hole transport layer;

[0164] (4') Depositing a back electrode material on the surface of the hole transport layer to obtain a back electrode and a formal single-junction perovskite solar cell.

[0165] In the method for preparing a single-junction perovskite solar cell of the present invention, the hole transport layer can be deposited by spin coating, scraping, physical vapor deposition (PVD), atomic layer deposition (ALD), slit coating or immersion; preferably, physical vapor deposition can be magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0166] In the method for preparing a single-junction perovskite solar cell of the present invention, the deposition method of the perovskite thin film layer can be spin coating, blade coating, electron beam evaporation, thermal evaporation, printing, spraying, spray pyrolysis or slit coating.

[0167] In the method for preparing a single-junction perovskite solar cell of the present invention, the electron transport layer can be deposited by spin coating, scraping, physical vapor deposition, atomic layer deposition, slit coating or immersion; preferably, physical vapor deposition can be magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0168] In the method for preparing a single-junction perovskite solar cell of the present invention, the preparation method of the perovskite precursor solution can be: mixing the raw materials of the perovskite structure material and the inorganic metal cyanate in a solvent to prepare the perovskite precursor solution.

[0169] In the method for preparing a single-layer perovskite solar cell of the present invention, the solvent in the perovskite precursor solution can be one or more selected from N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, 2-methoxyethanol, ethanol and isopropanol.

[0170] In the method for preparing a single-layer perovskite solar cell of the present invention, the concentration of the inorganic metal cyanate in the perovskite precursor solution can be 0.002-20 mg / mL, for example 0.005 mg / mL, 0.01 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 5 mg / mL, 10 mg / mL, 15 mg / mL, 20 mg / mL. The present invention controls the concentration of the inorganic metal cyanate in the perovskite precursor solution within the above range, which is beneficial to the film-forming crystallization quality of the perovskite film, and further helps to improve the efficiency and stability of the single-layer perovskite solar cell containing the perovskite film.

[0171] In the method for preparing a single-junction perovskite solar cell of the present invention, the back electrode can be deposited by physical vapor deposition, printing, spraying or electroplating; preferably, the physical vapor deposition can be magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0172] The present invention provides a method for preparing the tandem perovskite solar cell of the present invention, the method comprising the following steps:

[0173] (1) depositing a back electrode material and a tunneling layer material on two surfaces of the bottom battery to obtain a back electrode and an electron transport layer;

[0174] (2) depositing a hole transport layer material on the surface of the tunnel layer to obtain a hole transport layer;

[0175] (3) depositing a perovskite precursor solution on the surface of the hole transport layer to obtain a perovskite thin film layer;

[0176] (4) depositing an electron transport layer material on the surface of the perovskite thin film layer to obtain an electron transport layer;

[0177] (5) depositing a top electrode material on the surface of the electron transport layer to obtain an inverted stacked perovskite solar cell while obtaining the top electrode; or

[0178] (1') depositing a back electrode material and a tunneling layer material on two surfaces of the bottom battery respectively to obtain a back electrode and a hole transport layer;

[0179] (2') depositing an electron transport layer material on the surface of the tunneling layer to obtain an electron transport layer;

[0180] (3') depositing a perovskite precursor solution on the surface of the electron transport layer to obtain a perovskite thin film layer;

[0181] (4′) depositing a hole transport layer material on the surface of the perovskite thin film layer to obtain a hole transport layer;

[0182] (5') depositing a top electrode material on the surface of the hole transport layer to obtain a top electrode and a formal laminated perovskite solar cell;

[0183] In the present invention, the top electrode may include a transparent electrode layer; preferably, the top electrode may include a gate electrode and a transparent electrode layer in sequence from the light-receiving front side to the light-receiving back side, and more preferably, the top electrode may include a gate electrode, an anti-reflection layer and a transparent electrode layer in sequence from the light-receiving front side to the light-receiving back side.

[0184] In the method for preparing a laminated perovskite solar cell of the present invention, the back electrode can be deposited by physical vapor deposition, printing, spraying or electroplating; preferably, the physical vapor deposition can be magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0185] In the method for preparing a stacked perovskite solar cell of the present invention, the tunneling layer can be deposited by physical vapor deposition, single atomic layer deposition, chemical vapor deposition, plasma enhanced chemical vapor deposition or electron beam evaporation; preferably, physical vapor deposition is magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0186] In the method for preparing a stacked perovskite solar cell of the present invention, the hole transport layer can be deposited by spin coating, scraping, physical vapor deposition, atomic layer deposition, slit coating or immersion; preferably, physical vapor deposition can be magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0187] In the method for preparing a laminated perovskite solar cell of the present invention, the preparation method of the perovskite precursor solution can be: mixing the raw materials of the perovskite structure material and the inorganic metal cyanate in a solvent to prepare the perovskite precursor solution.

[0188] In the method for preparing a laminated perovskite solar cell of the present invention, the solvent in the perovskite precursor solution can be

[0189] The solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, 2-methoxyethanol, ethanol and isopropanol.

[0190] In the method for preparing a laminated perovskite solar cell of the present invention, the concentration of the inorganic metal cyanate in the perovskite precursor solution can be 0.002-20 mg / mL, for example 0.005 mg / mL, 0.01 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 5 mg / mL, 10 mg / mL, 15 mg / mL, 20 mg / mL. The present invention controls the concentration of the inorganic metal cyanate in the perovskite precursor solution within the above range, which is beneficial to the film-forming crystallization quality of the perovskite film, and further helps to improve the efficiency and stability of the laminated perovskite solar cell comprising the perovskite film.

[0191] In the method for preparing a laminated perovskite solar cell of the present invention, the deposition method of the perovskite thin film layer can be spin coating, blade coating, electron beam evaporation, thermal evaporation, printing, spraying, spray pyrolysis or slit coating.

[0192] In the method for preparing a stacked perovskite solar cell of the present invention, the electron transport layer can be deposited by spin coating, scraping, physical vapor deposition, atomic layer deposition, slit coating or immersion; preferably, physical vapor deposition can be magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0193] In the method for preparing a laminated perovskite solar cell of the present invention, the transparent electrode layer can be deposited by physical vapor deposition; preferably, the physical vapor deposition can be magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0194] In the method for preparing a stacked perovskite solar cell of the present invention, the anti-reflection layer can be deposited by physical vapor deposition; preferably, the physical vapor deposition can be magnetron sputtering, reactive plasma deposition, electron beam evaporation or thermal evaporation.

[0195] In the method for preparing a laminated perovskite solar cell of the present invention, the gate line electrode can be deposited by thermal evaporation, printing or electroplating.

[0196] Compared with the prior art, the present invention has the following beneficial effects:

[0197] (1) The present invention can significantly improve the film quality of the perovskite film by adding an inorganic metal cyanate additive to a solution containing a perovskite structure material, thereby improving the efficiency of the perovskite device;

[0198] (2) The present invention reduces lattice defects and forms a more stable crystal structure by doping specific inorganic metal ions into the perovskite crystal structure, thereby improving the stability of the device;

[0199] (3) The present invention significantly improves the efficiency and stability of perovskite devices prepared with different components and methods, and exhibits significant advantages in both single-junction and stacked cells.

[0200] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0201] Example 1

[0202] In this embodiment, the perovskite film is prepared, and the specific steps are as follows:

[0203] Take 88.3 mg of cesium iodide (CsI), 233.9 mg of iodomethane (FAI), 187.2 mg of lead bromide (PbBr2), 548.6 mg of lead iodide (PbI2) and sodium cyanate and dissolve them in a mixed solvent of 900 μL DMF and 100 μL DMSO. After fully dissolved, filter with a 250 μm oil filter to obtain a perovskite precursor solution. The perovskite precursor solution contains 1.7 mol / L of FA 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 )3 and 1mg / mL sodium cyanate; a perovskite film layer was prepared by a slit coating method on a clean glass substrate, and the specific operation was as follows: the height of the slit coating scraper from the glass substrate was 100μm, the wind knife angle was 45°, the wind knife pressure was 0.5MPa, the scraper speed was 5mm / s, the wind knife speed was 20mm / s, the injection speed was 5μL / s, after scraping the film, the film was transferred to a heating plate at 100°C and annealed for 10min to obtain a perovskite film layer, and the thickness of the perovskite film layer was 1500nm.

[0204] Example 2

[0205] The other conditions of this embodiment are the same as those of Embodiment 1, except that in this embodiment, the sodium cyanate in the perovskite precursor solution is replaced by potassium cyanate, and the concentration of potassium cyanate is 0.5 mg / mL.

[0206] Example 3

[0207] The other conditions of this embodiment are the same as those of Embodiment 1, except that in this embodiment, the sodium cyanate in the perovskite precursor solution is replaced with rubidium cyanate, and the concentration of rubidium cyanate is 10 mg / mL.

[0208] Example 4

[0209] The other conditions of this embodiment are the same as those of Embodiment 1, except that in this embodiment, the sodium cyanate in the perovskite precursor solution is replaced with cesium cyanate, and the concentration of cesium cyanate is 20 mg / mL.

[0210] Example 5

[0211] The other conditions of this embodiment are the same as those of Embodiment 1, except that in this embodiment, the sodium cyanate in the perovskite precursor solution is replaced by calcium cyanate, and the concentration of calcium cyanate is 0.1 mg / mL.

[0212] Example 6

[0213] The other conditions of this embodiment are the same as those of Embodiment 1, except that in this embodiment, the sodium cyanate in the perovskite precursor solution is replaced by zinc cyanate, and the concentration of zinc cyanate is 0.2 mg / mL.

[0214] Example 7

[0215] The other conditions of this embodiment are the same as those of Embodiment 1, except that in this embodiment, the sodium cyanate in the perovskite precursor solution is replaced with cobalt cyanate, and the concentration of cobalt cyanate is 0.002 mg / mL.

[0216] Example 8

[0217] The other conditions of this embodiment are the same as those of Embodiment 1, except that in this embodiment, the sodium cyanate in the perovskite precursor solution is replaced with europium cyanate, and the concentration of europium cyanate is 5 mg / mL.

[0218] Example 9

[0219] The other conditions of this embodiment are the same as those of Embodiment 1, except that in this embodiment, the sodium cyanate in the perovskite precursor solution is replaced with cerium cyanate, and the concentration of cerium cyanate is 3 mg / mL.

[0220] Comparative Example 1

[0221] The other conditions of the comparative example are the same as those of Example 1, except that the perovskite precursor solution of this comparative example does not contain inorganic metal cyanate.

[0222] Example 10

[0223] In this embodiment, the structure is prepared as Figure 1 The single-junction perovskite solar cell shown in the figure has the following specific steps:

[0224] 1. Dissolve [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACZ) in ethanol to prepare a MeO-2PACZ solution with a concentration of 1 mmol / mL. Take 130 μL of the MeO-2PACZ solution and drop it on a cleaned ITO glass with a size of 2.5 cm*2.5 cm, then spin coat it at a speed of 4000 rpm for 15 seconds. After the spin coating is completed, transfer it to a hot plate at 100°C for annealing for 10 minutes, and then remove it to obtain a hole transport layer with a thickness of 2 nm.

[0225] 2. Take 19.5 mg of cesium iodide (CsI), 232.2 mg of iodomethane (FAI), 11.9 mg of iodomethane (MAI), 691.5 mg of lead iodide (PbI2) and sodium cyanate and dissolve them in a mixed solvent of 800 μL of DMF and 200 μL of DMSO. After fully dissolved, filter with a 250 μm oil filter to obtain a perovskite precursor solution. The perovskite precursor solution contains 1.5 mol / L of FA 0.9 MA 0.05 Cs 0.05 PbI3 (FAMACs) and 1 mg / mL sodium cyanate; a perovskite film layer was prepared by spin coating, and the specific operation was as follows: the perovskite precursor solution was placed in a glove box for spin coating, 100 μL of the perovskite precursor solution was first dripped on the surface of the hole transport layer, and the spin coating was performed according to the process of 2000 rpm for 10 s and 6000 rpm for 30 s for a total of 40 s, and 300 μL of anisole solution (anti-solvent) was sucked with a 1 μL pipette tip, and the anisole solution was dripped when the perovskite solution was spin coated for 30 s, and the film was removed from the spin coater after the spin coating stopped, and heated on a heating plate at 100°C for 10 min to obtain a perovskite film layer, and the thickness of the perovskite film layer was 600 nm;

[0226] 3. Fullerene (C60) is deposited on the surface of the perovskite film layer by thermal evaporation to obtain a fullerene layer with a thickness of 25 nm; tin dioxide (SnO2) is deposited on the fullerene surface by atomic layer deposition to obtain a tin dioxide layer with a thickness of 20 nm. The fullerene layer and the tin dioxide layer together constitute an electron transport layer. During the thermal evaporation process, the temperature of the evaporation source is 450°C and the evaporation rate is 0.1 A / s;

[0227] 4. The thermal evaporation method is used to deposit metallic copper on the surface of the electron transport layer to obtain a back electrode and a single-junction perovskite solar cell. The thickness of the back electrode is 200 nm.

[0228] Embodiment 11

[0229] The other conditions of this embodiment are the same as those of embodiment 10. The only difference is that in this embodiment, the perovskite

[0230] Sodium cyanate in the flooding solution was replaced by potassium cyanate, and the concentration of potassium cyanate was 0.2 mg / mL.

[0231] Example 12

[0232] The other conditions of this embodiment are the same as those of Embodiment 10, except that in this embodiment, the sodium cyanate in the perovskite precursor solution is replaced by rubidium cyanate, and the concentration of rubidium cyanate is 0.5 mg / mL.

[0233] Example 13

[0234] The other conditions of this embodiment are the same as those of Embodiment 10, except that in this embodiment, the sodium cyanate in the perovskite precursor solution is replaced with cesium cyanate, and the concentration of cesium cyanate is 10 mg / mL.

[0235] Comparative Example 2

[0236] The other conditions of this comparative example are the same as those of Example 10, except that the solute in the perovskite precursor solution in this comparative example is only FAMACs, and does not contain sodium cyanate.

[0237] Embodiment 14

[0238] The other conditions of this embodiment are the same as those of embodiment 1, except that in this embodiment, step (2) is as follows: 77.9 mg of cesium iodide (CsI), 206.4 mg of iodomethane (FAI), 691.5 mg of lead iodide (PbI2) and calcium cyanate are dissolved in a mixed solvent of 800 μL of DMF and 200 μL of DMSO, and after being fully dissolved, the mixture is filtered using a 250 μm oily filter to obtain a perovskite precursor solution, which contains 1.5 mol / L of FA 0.8 Cs 0.2 PbI3(FACs) and 2mg / mL calcium cyanate; the perovskite thin film layer was prepared by a slit coating method, and the specific operation was as follows: the height of the slit coating scraper from the glass substrate was 100μm, the wind knife angle was 45°, the wind knife pressure was 1MPa, the scraper movement speed was 15mm / s, the wind knife movement speed was 10mm / s, the liquid injection speed was 7.5μL / s, and after scraping the film, the film was transferred to a heating plate at 100°C and annealed for 10 minutes to obtain a perovskite thin film layer with a thickness of 2000nm.

[0239] Embodiment 15

[0240] The other conditions of this embodiment are the same as those of Embodiment 14, except that in this embodiment, the calcium cyanate in the perovskite precursor solution is replaced by zinc cyanate, and the concentration of zinc cyanate is 0.5 mg / mL.

[0241] Example 16

[0242] The other conditions of this embodiment are the same as those of Embodiment 14, except that in this embodiment, the calcium cyanate in the perovskite precursor solution is replaced with europium cyanate, and the concentration of europium cyanate is 0.2 mg / mL.

[0243] Embodiment 17

[0244] The other conditions of this embodiment are the same as those of Embodiment 14, except that in this embodiment, calcium cyanate in the perovskite precursor solution is replaced with cerium cyanate, and the concentration of cerium cyanate is 1 mg / mL.

[0245] Comparative Example 3

[0246] The other conditions of this comparative example are the same as those of Example 14, except that the solute in the perovskite precursor solution in this comparative example is only FACs and does not contain calcium cyanate.

[0247] Embodiment 18

[0248] The structure of the crystalline silicon / perovskite tandem solar cell of this embodiment is as follows: Figure 3 As shown, the preparation process is as follows:

[0249] 1. Preparation of bottom cell: Using plasma enhanced chemical vapor deposition (PECVD) process, intrinsic amorphous silicon layers (a-Si(i)) are deposited on both sides of the intrinsic silicon layer (c-Si(n)) at 200°C to obtain a passivation layer, and then n-type microcrystalline silicon layers and p-type microcrystalline silicon layers are deposited on both sides of the passivation layer to obtain an electron transport layer (nc-Si(p)) and a hole transport layer (nc-Si(p)), respectively, to obtain a bottom cell. The thickness of the bottom cell is 300μm.

[0250] 2. Preparation of back electrode and tunneling layer: ITO is deposited on the surface of p-type microcrystalline silicon layer by magnetron sputtering to obtain a transparent electrode layer with a thickness of 80nm, and silver is printed on the surface of transparent electrode layer by printing to obtain a silver grid electrode with a height of 20μm and a width of 30μm. The transparent electrode layer and the silver grid electrode constitute the back electrode; ITO is deposited on the surface of n-type microcrystalline silicon layer by magnetron sputtering to obtain a tunneling layer with a thickness of 20nm;

[0251] 3. Dissolve [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACZ) in ethanol to prepare a MeO-2PACZ solution with a concentration of 1 mmol / mL, take 130 μL of MeO-2PACZ solution and drop it on the surface of the tunneling layer ITO, then spin coat it at a speed of 4000 rpm for 15 seconds, transfer it to a hot plate at 100°C after spin coating, anneal it for 10 minutes, and then remove it to obtain a hole transport layer with a thickness of 2 nm;

[0252] 4. Take 88.3 mg of cesium iodide (CsI), 233.9 mg of iodomethane (FAI), 187.2 mg of lead bromide (PbBr2), 548.6 mg of lead iodide (PbI2) and calcium cyanate and dissolve them in a mixed solvent of 800 μL DMF and 200 μL DMSO. After fully dissolved, filter with a 250 μm oil filter to obtain a perovskite precursor solution. The perovskite precursor solution contains 1.7 mol / L of FA 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 )3 and 2mg / mL of copper cyanate; a perovskite film layer was prepared by a scraping method; the specific operation was as follows: 10μL of perovskite precursor was dropped on the scraper head, the scraper moved at a speed of 5-30mm / s, the scraper height was 50-150um, and after scraping, a N2 air knife was used to blow, the blowing pressure was 0.5-1.5Mpa, the moving speed was 5-30mm / s, and after blowing, the perovskite film was annealed on a heating plate at 100°C for 10min to obtain a perovskite film layer, and the thickness of the perovskite film layer was 1500nm;

[0253] 5. Fullerene (C60) is deposited on the surface of the perovskite film layer by thermal evaporation to obtain a fullerene layer with a thickness of 12 nm; tin dioxide (SnO2) is deposited on the fullerene surface by atomic layer deposition to obtain a tin dioxide layer with a thickness of 20 nm. The fullerene layer and the tin dioxide layer together constitute an electron transport layer. During the thermal evaporation process, the temperature of the evaporation source is 450°C and the evaporation rate is 0.1 A / s;

[0254] 6. IZO is deposited on the surface of the electron transport layer by magnetron sputtering to obtain a transparent conductive layer with a thickness of 70 nm; MgF2 is deposited on the surface of the transparent conductive layer by thermal evaporation to obtain an anti-reflection layer with a thickness of 120 nm; finally, silver is deposited on the surface of the anti-reflection layer by thermal evaporation to obtain a 800 nm silver grid electrode. The transparent conductive layer, the anti-reflection layer and the silver grid electrode together constitute the top electrode, and a crystalline silicon / perovskite stacked solar cell is obtained.

[0255] Embodiment 19

[0256] The other conditions of this embodiment are the same as those of Embodiment 18, except that in this embodiment, the copper cyanate in the perovskite precursor solution is replaced by cobalt cyanate, and the concentration of cobalt cyanate is 1 mg / mL.

[0257] Comparative Example 4

[0258] The other conditions of this comparative example are the same as those of Example 18, except that the solute in the perovskite precursor solution in this comparative example is only FA 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 )3, does not contain copper cyanate.

[0259] Test Case

[0260] Crystallization test of perovskite film layer: X-ray diffraction was performed on the perovskite films obtained in Examples 1-3, Example 6, Examples 8-9 and Comparative Example 1. The X-ray diffractometer was a D2 X-ray diffractometer from Bruker. The energy of the X-ray was 8 keV. The test angle range was 5° to 30°. The test speed was 0.02° / s. The test results are shown in FIG. Figure 4 As shown; the perovskite films prepared in Examples 1-9 and Comparative Example 1 were subjected to fluorescence tests, the fluorescence excitation light wavelength was 450nm, the test camera was a CCD camera, the pixel size was 20μm, the test integration time was 2s, and the test results Figure 5 shown.

[0261] Initial performance test of perovskite solar devices: At 25°C and AM 1.5G standard solar spectrum, a solar simulator was used to set the voltage range to 2V to -0.5V, and the current output of the perovskite solar cells prepared in Examples 10-19 and Comparative Examples 2-4 at different voltages was tested, and the corresponding current-voltage (IV) characteristic curves were plotted, where the cell surface area was 1.1664cm 2 , the incident light power (Pin) is 100mW / cm 2 The characteristic curve at this time is the characteristic curve of initial performance, and the initial performance (initial open circuit voltage, initial short circuit current density, initial fill factor and initial photoelectric conversion efficiency) of the perovskite solar cells prepared in Examples 10-19 and Comparative Examples 2-4 are obtained based on the characteristic curve of initial performance.

[0262] (1) Open circuit voltage (Voc): The voltage value corresponding to when the current is equal to zero.

[0263] (2) Short-circuit current density (Jsc): The current value when the voltage is zero is the short-circuit current (Isc), and the current per unit battery surface area is the short-circuit current density.

[0264] (3) Fill factor (FF): The ratio of the maximum output power (Pmax) of the battery to the product of the open circuit voltage and the short circuit current. The calculation formula is (Pmax / Voc*Isc), where the maximum power point is the point where the battery output power reaches its maximum value.

[0265] (4) Photoelectric conversion efficiency (PCE): Photoelectric conversion efficiency refers to the ratio of maximum output power to incident light power (Pin), and the calculation formula is (Pmax / Pin)*100%.

[0266] Aging performance test of perovskite solar cell devices: The perovskite solar cells prepared in Examples 10-19 and Comparative Examples 2-4 were aged for 100 h at 85°C and AM 1.5G in an open circuit. A solar simulator was used to set the voltage range to 2V to -0.5V. The current output of the perovskite solar cells prepared in Examples 10-19 and Comparative Examples 2-4 at different voltages was tested, and the corresponding current-voltage (IV) characteristic curves were plotted. The cell surface area was 1.1664 cm 2 , the incident light power (Pin) is 100mW / cm 2 The characteristic curve at this time is the characteristic curve of aging performance, and the aging performance (open circuit voltage after aging, short circuit current density after aging, fill factor after aging, and photoelectric conversion efficiency after aging) of the perovskite solar cells prepared in Examples 10-19 and Comparative Examples 2-4 are obtained from the characteristic curve of aging performance.

[0267] Efficiency ratio of perovskite solar devices: efficiency ratio = initial photoelectric conversion efficiency / photoelectric conversion efficiency after aging × 100%.

[0268] The test results of initial performance, aging performance and efficiency ratio of the single-junction perovskite solar cells prepared in Examples 10-17 and Comparative Examples 2-3 are shown in Table 1; the test results of initial performance, aging performance and efficiency ratio of the stacked perovskite solar cells prepared in Examples 18-19 and Comparative Example 4 are shown in Table 2.

[0269] Table 1: Initial performance, aging performance and efficiency ratio of single-junction perovskite solar cells prepared in Examples 10-17 and Comparative Examples 2-3

[0270]

[0271] Table 2: Initial performance, aging performance and efficiency ratio of the laminated perovskite solar cells prepared in Examples 18-19 and Comparative Example 4

[0272]

[0273] Figure 4The X-ray diffraction patterns of the perovskite films prepared in Examples 1-3, Example 6, Examples 8-9 and Comparative Example 1 are shown in FIG. Figure 4 It can be seen that the peak at 14.2° represents the peak of perovskite. The stronger the peak, the higher the crystallinity of the perovskite. The inorganic metal cyanate additive of the present invention can significantly improve the crystallization quality of perovskite.

[0274] Figure 4 The fluorescence images of the perovskite films obtained in Examples 1-9 and Comparative Example 1 show that the improvement of the crystallization quality of the perovskite film will eventually be reflected in the reduction of non-radiative recombination of the film. This phenomenon can be judged by the fluorescence intensity. The stronger the fluorescence, the lower the non-radiative recombination. Figure 5 It can be seen that although the degree of improvement in fluorescence intensity of perovskite films with the addition of inorganic metal cyanates is different, they can all bring different degrees of improvement to the perovskite films. Among them, potassium cyanate, cesium cyanate, calcium cyanate, europium cyanate and cerium cyanate can significantly improve the fluorescence intensity.

[0275] As can be seen from Table 1, compared with Comparative Example 2 in which there is no additive in the perovskite film, Examples 10-13 having an inorganic metal cyanate additive in the perovskite film have higher efficiency and stability. Compared with Comparative Example 3 in which there is no additive in the perovskite film, Examples 14-17 having an inorganic metal cyanate additive in the perovskite film have higher efficiency and stability. It can be seen that the inorganic metal cyanate additive of the present invention can improve the efficiency and stability of the perovskite device. Further, the preparation method of the perovskite film of Examples 10-13 and Comparative Example 2 is a spin coating method, and the component includes MA. The preparation method of the perovskite film of Examples 14-17 and Comparative Example 3 is a slit coating method, and the component does not include MA. It can be seen that the present invention has significantly improved the efficiency and stability of perovskite devices prepared by different components and different methods.

[0276] As can be seen from Table 2, compared with Comparative Example 4 in which there is no additive in the perovskite film, Examples 18-19 having an inorganic metal cyanate additive in the perovskite film have higher efficiency and stability. The perovskite films of Examples 10-17 and Comparative Examples 2-3 are located in a single-junction perovskite solar cell, and the perovskite films of Examples 18-19 and Comparative Example 4 are located in a laminated perovskite solar cell. It can be seen that the single-junction perovskite solar cell and the laminated perovskite solar cell of the present invention have significantly improved efficiency and stability.

[0277] In summary, inorganic metal cyanates improve the crystallization quality of perovskite, thereby reducing non-radiative recombination in perovskite films and ultimately improving the performance of perovskite devices.

Claims

1. A perovskite film, characterized in that: The perovskite film comprises a perovskite structural substance and an inorganic metal cyanate, wherein the metal in the inorganic metal cyanate is selected from one or more of an alkali metal, an alkaline earth metal, a transition metal and a rare earth metal.

2. The perovskite film according to claim 1, characterized in that The perovskite film has one or more of the following characteristics: The inorganic metal cyanate is selected from one or more of lithium cyanate, sodium cyanate, potassium cyanate, rubidium cyanate, cesium cyanate, magnesium cyanate, calcium cyanate, barium cyanate, zinc cyanate, cobalt cyanate, copper cyanate, europium cyanate, cerium cyanate and lanthanum cyanate; The chemical formula of the perovskite structure material is ABX3, wherein A is a monovalent cation, including one or more of cesium, rubidium, methylamine and methylamidine, B is a divalent cation, including one or more of lead, copper, zinc, gallium, tin and calcium, and X is a monovalent anion, including one or more of iodine, bromine, chlorine, fluorine, thiocyanate, tetrafluoroborate, hexafluorophosphate, formate and acetate; The mass ratio of the inorganic metal cyanate to the perovskite structure material is ≤5.5%; The thickness of the perovskite film is 200-10000 nm.

3. A method for preparing a perovskite film, characterized in that: The method comprises the following steps: mixing raw materials of perovskite structure material and inorganic metal cyanate in a solvent to prepare a perovskite precursor solution, and depositing the perovskite precursor solution to obtain a perovskite film.

4. The method according to claim 3, characterized in that The method has one or more of the following features: The solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, 2-methoxyethanol, ethanol and isopropanol; The method of depositing the perovskite precursor solution is spin coating, doctor blade coating, electron beam evaporation, thermal evaporation, printing, spraying, spray pyrolysis or slit coating; The concentration of the inorganic metal cyanate in the perovskite precursor solution is 0.002-20 mg / mL.

5. A photoelectric device, characterized in that: The optoelectronic device comprises a perovskite film, and the perovskite film comprises a perovskite structural substance and an inorganic metal cyanate.

6. The optoelectronic device according to claim 5, characterized in that The perovskite solar device includes a single-junction perovskite solar cell and / or a stacked perovskite solar cell.

7. The optoelectronic device according to claim 5, characterized in that In the single-junction perovskite solar cell or the stacked perovskite solar cell, the thickness of the perovskite film is 200-3000 nm.

8. A method for preparing the optoelectronic device according to any one of claims 5 to 7, characterized in that: The method comprises the following steps: (1) depositing a hole transport layer or an electron transport layer on the surface of the transparent conductive glass; (2) depositing a perovskite thin film layer on the surface of the hole transport layer or the electron transport layer; (3) depositing an electron transport layer or a hole transport layer on the surface of the perovskite thin film layer; (4) depositing a back electrode on the surface of the electron transport layer or the hole transport layer to obtain a single-junction perovskite solar cell; or (1') depositing a back electrode material and a tunneling layer on two surfaces of the bottom cell respectively; (2') Depositing a hole transport layer or an electron transport layer on the surface of the tunnel layer (3') depositing a perovskite thin film layer on the surface of the hole transport layer or the electron transport layer; (4') depositing an electron transport layer or a hole transport layer on the surface of the perovskite thin film layer; (5') depositing a top electrode on the surface of the electron transport layer or the hole transport layer to obtain a stacked perovskite solar cell.

9. The method according to claim 8, characterized in that The method has one or more of the following features: In step (2) or step (3'), a perovskite precursor solution is deposited on the surface of the hole transport layer or the electron transport layer to obtain a perovskite film layer, wherein the perovskite precursor solution comprises a raw material of a perovskite structure material, an inorganic metal cyanate and a solvent.

10. The method according to claim 7, characterized in that The method has one or more of the following features: The method for preparing the perovskite precursor solution is as follows: mixing the raw material of the perovskite structure material and the inorganic metal cyanate in a solvent to prepare the perovskite precursor solution; The solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, 2-methoxyethanol, ethanol and isopropanol; The concentration of the inorganic metal cyanate in the perovskite precursor solution is 0.002-20 mg / mL; The deposition method of the perovskite thin film layer is spin coating, blade coating, electron beam evaporation, thermal evaporation, printing, spraying, spray pyrolysis or slit coating.

Citation Information

Cited By

  • Perovskite thin film and preparation method therefor, and photoelectric device and preparation method therefor

    WO2026052150A1